Current management and future perspectives of metastatic renal cell carcinoma. (27th May 2014) - Lee‐Ying, Richard; Lester, Renee; Heng, Daniel YC
Abstract Over the last number of years, the treatment of metastatic renal cell cancer has evolved tremendously with the advent of targeted therapy. Previously, immunotherapies, such as interferon alpha and interleukin‐2, were the only treatment options available for this chemoresistant malignancy. Currently, seven additional agents, including sunitinib, sorafenib, axitinib, pazopanib, bevacizumab, everolimus and temsirolimus, have been approved for use in metastatic renal cell cancer, with several more in development. The efficacy of these agents depends primarily on inhibition of the vascular endothelial growth factor and mammalian target of rapamycin pathways, and have drastically improved the outcomes of patients diagnosed with metastatic renal cell cancer. This article reviews the major treatment advances that have occurred for metastatic renal cell cancer with the advent of targeted treatments, summarizes the evidence to support their use and addresses clinical issues that have arisen with them. To help guide clinicians in their decision‐making with these emerging therapeutic choices, the evidence for sequencing and combining these agents, and the need for biomarkers will be addressed. The role of surgical management options, such as cytoreductive nephrectomy and metastectomy, in the era of targeted treatment is also reviewed. Several novel treatments are also on the horizon, which might serve as future avenues for treatment advancement in metastatic renal cell cancer.